A game between green and non-green supply chains considering two-way government intervention and manufacturer competition - Shang, Wenfang; Wang, Bingyan; Xia, Defeng (Frontiers in Environmental Science, 2022)
Enterprise competition has been transformed into chain-to-chain competition, and green development is imperative under the promotion of policies. Horizontal cooperation between green and non-green manufacturers provides a new direction for the supply chain to improve its core competitiveness. This paper develops competition and cooperation models between two manufacturers for the green and non-green supply chain under two-way government intervention to explore the impact of manufacturers’ horizontal cooperation on decisions and profits of supply chain members. In particular, for a situation without cooperation, we consider a Stackelberg game between two manufacturers. Model solutions and numerical analysis have shown that: (1) Cooperation among manufacturers can not only improve their own profits, but also strengthen environmental welfare. However, cooperation will damage consumer surplus. (2) When consumers are more sensitive to product prices, manufacturers' cooperative behavior is not conducive to retailers, but with the improvement of consumer environmental awareness, retailers will gradually support their upstream cooperation. (3) Under the simultaneous implementation of government subsidy and punishment strategies, whether green consumption can be promoted is related to the adjustment factor of government subsidies, while the relationship between the green level floor for subsidy and product greenness is affected by the adjustment factor of subsidies and manufacturers’ cooperation. (4) The impacts of fierce price competition and green level competition on supply chain members are opposite; when the price competition is moderate or the green level competition is weak, the manufacturers’ cooperation is also beneficial to the improvement of retailers’ profits. This provides ideas for the development of green supply chain, and provides a reference for the implementation of two-way government intervention policy.